The Effect of Perception about The Educational Services Quality and Organizational Environment on Students' Achievement Motivation in Environmental Health Department - Ismi Trihardini; M. Asrori; M. Syukri (STKIP Singkawang, 2019)
Achievement motivation is an urge in a person to compete and become superior. Achievement motivation is needed so that students have the drive to compete with excellence standards, where this achievement motivation plays a role in developing activities and initiatives, directing and maintaining perseverance in learning activities. Motivation between one student and another student is different due to different perceptions of the quality of educational services. The environment around the education process that can be said as a conducive organizational environment plays a role in increasing the drive for the achievement of students. This study aims to describe and analyze the influence of perceptions about the quality of education services and organizational environment on achievement motivation. The approach in this study is quantitative in the form of causal studies, a sample of 68 students in the Department of Environmental Health of the Ministry of Health of Pontianak were taken using the proportionate stratified random sampling technique. Data retrieval is done by using a research instrument in the form of questionnaire which refers to the Likert scale. Data were analyzed using Rank Spearman test and Linear Regression. Descriptive analysis explained that perception variables about the quality of education services and organizational environment were very good, and achievement motivation was very high. The results of correlation analysis describe 1) student perceptions about the quality of education services significantly influence achievement motivation (r = 0.445), 2) Organizational environment significantly influences achievement motivation (r = 0.767) 3) Student perceptions of the quality of educational services and organizational environment collectively have a significant effect on student achievement motivation in the Department of Health Polytechnic of the Ministry of Health of Pontianak (R = 0.779). Conclusions from this study are student perceptions of the quality of education services and organizational environment affect the achievement motivation. Based on the results of the study, it is suggested that the Health Department of Pontianak Health Ministry Polytechnic should continue to maintain or even improve the quality of education services and organizationalenvironment by taking into account the advice provided by the school component through the suggestion box.